Calculation of energy loss of proton beam on thyroid tumor - Giri, K.; Paudel, B.; Gautam, B.R. (Himalayan Physics, 2020)
Proton beam therapy is an emerging technique in radiotherapy. The Bragg peak of a proton enables it to lose most of its energy to the targeted tissue like tumor cells, with less impact of healthy tissues and organs. This property of a proton beam makes it ideal for clinical applications. When organ safekeeping is our priority then proton beam therapy is the most effective tool to damage nearby affected tissues. For efficient treatment planning in thyroid tumor, the maximal energy loss of proton beam in its tissues must be exactly calculated. The method of computer simulation is employed for the calculation of energy loss by energized proton beam irradiation on thyroid tumor at a depth of 22 mm. The stopping power and range data agrees with standard reference data. Of the 50 MeV energy of proton beam, the most of the energy is absorbed on various layers viz. skin, adipose tissue, skeletal muscles and thyroid which are approximately 1.5 MeV, 5.3 MeV, 10.5 MeV and 33.5 MeV respectively. In total 99.96% of energy of proton beam is absorbed by the targeted tissues.